Impact of cannabis use on prefrontal and parietal cortex gyrification and surface area in adolescents and emerging adults - Skyler G. Shollenbarger; Jenessa Price; Jon Wieser; Krista Lisdahl (Developmental Cognitive Neuroscience, 2015)
Background: Regions undergoing maturation with CB1 receptors may be at increased risk for cannabis-induced alterations. Here, we examine the relationships between cannabis use and prefrontal (PFC) and inferior parietal gyrification and surface area (SA) in youth. Methods: Participants included 33 cannabis users and 35 controls (ages 18–25). Exclusions included co-morbid psychiatric/neurologic disorders and heavy other drug use. Multiple regressions and Pearson r correlations examined the effects of cannabis use on gyrification, SA and cognition. Results: Cannabis use was associated with decreased gyrification in: ventral-medial PFC (RH: [FDR corrected p = .02], LH: [FDR corrected p = .02]); medial PFC (RH: [FDR corrected p = .02], LH: [FDR corrected p = .02]); and frontal poles (RH: [FDR corrected p = .02], LH: [FDR corrected p = .02]). No differences were observed in bilateral hemispheres, PFC, dorsolateral, ventrolateral, or inferior parietal ROIs. Cannabis use was associated with marginally decreased SA in left: medial PFC [FDR corrected p = .09], and ventral lateral PFC: [FDR corrected p = .09]. In cannabis users, increased gyrification was associated with improved working-memory performance in right medial (p = .003), ventral-medial (p = .03), and frontal pole ROIs (p = .007). Conclusions: Cannabis use was associated with reduced gyrification in PFC regions implicated in self-referential thought and social cognition. Results suggest that these gyrification characteristics may have cognitive implications.